Effects of Stocking Density on Growth Performance of Litopenaeus Vannamei Under Low and High Salinity Pond Culture During the Second Crop Of 2019 in Andhra Pradesh, India (International Journal of Environmental Sciences, 2024)
This study conducted an independent aquaculture experiment focused on Litopenaeus vannamei farmed in the second crop of 2019 in Krishna District, Andhra Pradesh, India. The core objective of the research was to assess the growth rate of the shrimp under different stocking densities in low-salinity and high-salinity ponds. This study set up in four different types of water quality conditions like low-salinity low-density, low-salinity high-density, high-salinity low-density and high-salinity high-density. The average measured values of five core water quality indicators, namely pH, salinity, dissolved oxygen, ammonia nitrogen, and temperature, were collected for all four groups of ponds. The study ultimately derived the core conclusion that stocking density is negatively correlated with the shrimp’s growth performance. It clarifies that low stocking density is more conducive to the growth and production of the shrimp, while high stocking density reduces production efficiency. The findings of this study hold important guiding significance for the sustainable farming of Litopenaeus vannamei under different salinity conditions.